Adsorption Of Heavy Metals Onto Waste Tea - Sukru Aslan; Sayiter Yildiz; Mustafa Ozturk; Ayben Polat (European Scientific Journal, ESJ, 2016)
Adsorption of Ni (II) and Cu (II) on the waste tea materials were studied at various temperatures and pHs. The maximum adsorption capacities of tea materials were as determined at the pH and temperature of 5.0 and 50 0C. Adsorption capacity of tea is more affected from pH than temperature. At the end of the batch experiments, concentration of NH4-N was lower than 1.0 mg/L. However, COD concentrations were increased from 88 mg/L to 96 mg/L by increasing temperatures from 30 to 50 0C, respectively. The highest organic matter release from the sorbent was observed at the pH of 2.0.